Post-9/11 US Policies and South Asia - Umbreen Javaid (Journal of Political Studies, 2014)
The administration in the US has made up its mind with regard to rectifying its policies towards the South Asian region. The extremist forces, having established their credentials as a global risk, remain a serious threat to global peace and stability. The Obama administration is especially concentrating on the South Asian region, keeping in mind its colossal strategic significance. Recently, Washington executed her new policy on the issue of how to handle the Taliban in Afghanistan. The US has also persuaded India and Pakistan, two central regional stakeholders, about her benefits in Afghanistan. The US has to understand the interests of both Pakistan and India, two nuclear antagonistic neighbours in the region, when it comes to resolving the Afghanistan issue. Pakistan is anxious about her relative strategic depth, the unsettled Kashmir issue and oppressive Indian objectives. In addition to all this, the US administration has accepted the responsibility, before the international community, of dealing with the challenges of extremist forces in the South Asian region.